2018
DOI: 10.1007/s10637-018-0646-1
|View full text |Cite
|
Sign up to set email alerts
|

First-in-human study of the anti-HB-EGF antibody U3-1565 in subjects with advanced solid tumors

Abstract: U3-1565 is a monoclonal antibody directed against heparin-binding epidermal growth factor-like growth factor (HB-EGF), which mediates angiogenesis via induction of vascular endothelial growth factor (VEGF-A). This first-in-human study characterized the safety, tolerability, efficacy, pharmacokinetics, and pharmacodynamics of U3-1565 in subjects with advanced solid tumors. In Part 1 (dose escalation following a modified 3 + 3 design), Cohorts 1-4, U3-1565 was administered at 2, 8, 16, and 24 mg/kg every 3 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It became evident that soluble HB-EGF (sHB-EGF) promotes tumor progression ( 57 ), and HB-EGF inhibition has been validated in vitro as a possible therapeutic target in ovarian, breast, bladder, and gastric cancer cells ( 58 ). Different sHB-EGF–blocking strategies have been developed to inhibit its binding to EGFR, including monoclonal antibodies ( 59 , 60 ), a nontoxic mutant of diphtheria toxin ( 61 ), the recombinant prodomain of ADAM12 ( 62 ), and small inhibitory peptides ( 63 ). A first-in-human study with the anti–HB-EGF antibody U3-1565, conducted in a small patient cohort with solid tumors, demonstrated an antitumor response and no dose-limited toxicity ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It became evident that soluble HB-EGF (sHB-EGF) promotes tumor progression ( 57 ), and HB-EGF inhibition has been validated in vitro as a possible therapeutic target in ovarian, breast, bladder, and gastric cancer cells ( 58 ). Different sHB-EGF–blocking strategies have been developed to inhibit its binding to EGFR, including monoclonal antibodies ( 59 , 60 ), a nontoxic mutant of diphtheria toxin ( 61 ), the recombinant prodomain of ADAM12 ( 62 ), and small inhibitory peptides ( 63 ). A first-in-human study with the anti–HB-EGF antibody U3-1565, conducted in a small patient cohort with solid tumors, demonstrated an antitumor response and no dose-limited toxicity ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different sHB-EGF–blocking strategies have been developed to inhibit its binding to EGFR, including monoclonal antibodies ( 59 , 60 ), a nontoxic mutant of diphtheria toxin ( 61 ), the recombinant prodomain of ADAM12 ( 62 ), and small inhibitory peptides ( 63 ). A first-in-human study with the anti–HB-EGF antibody U3-1565, conducted in a small patient cohort with solid tumors, demonstrated an antitumor response and no dose-limited toxicity ( 60 ). In the future, it would be interesting to analyze the effect of U3-1565 on the TME and evaluate whether this treatment could enhance the effect of immune checkpoint inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirmed that HBEGF neutralizing antibody could attenuate sorafenib-induced stratum corneum thickening in mice. However, the HBEGF antibody is still under phase I trial, 71 and the date of its clinical approval is yet undetermined. Meanwhile, the combined usage of EGFR inhibitor and sorafenib may lead to severe adverse reactions including pulmonary toxicity and hepatotoxicity, 72,73 and no specific JNK2-inhibiting compound has yet been identified.…”
Section: Discussionmentioning
confidence: 99%